The Impact of Growth Mindset Interventions on Students’ Motivation, Resilience, and Academic Achievement - Mohamoud, Ahmed Madey (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focuses on the impact of growth mindset interventions on students’ motivation, resilience and academic achievement. The specific objectives of the study entail: to assess the impacts of growth mindset interventions on student motivation, resilience, and academic performance in educational settings, to examine the practical strategies employed by educators to implement growth mindset interventions effectively and to identify potential challenges and limitations of growth mindset interventions in fostering a growth mindset culture in schools. The study employed qualitative research approach and used documentary review to collect data of the study. The findings of the study on the impact of growth mindset interventions on students’ motivation, resilience and academic achievement revealed that growth mindset interventions have demonstrated significant positive impacts on students' motivation in educational settings, evidence from various studies demonstrates that growth mindset interventions have a positive impact on students' resilience in educational settings and lastly various recent research studies conducted provide evidence of the positive impact of growth mindset interventions on students' academic achievement, motivation, engagement, resilience, and persistence. The findings of the study on the practical strategies employed by educators to implement growth mindset interventions effectively entail: provision of explicit instruction, fostering a supportive classroom culture, teaching effective learning strategies, provision of feedback that promotes growth mindset, encouragement of reflection and metacognition, modelling a growth mindset and leverage of technology and digital resources: The findings of the study on the potential challenges and limitations of growth mindset interventions in fostering a growth mindset culture in schools include: limited sustainability, individual differences, low teacher training, contextual factors and overgeneralization. The study recommends that Schools and educational institutions should actively incorporate growth mindset interventions into their curriculum and teaching strategies, encouraged to set realistic and achievable goals and regularly reflect on their progress, provide professional development opportunities and training programs for educators to enhance their understanding of growth mindset principles and strategies and should create an environment that promotes positivity, encouragement, and a sense of belonging.